Chromatographic method for the simultaneous quantification of dapsone and clofazimine in nanoformulations. Issue 17 (29th July 2018) - Machado, Sandia; Fernandes, Sara R.; Chaves, Luise L.; Lima, Sofia A. C.; Silva, Eduarda M. P.; Barreiros, Luísa; Reis, Salette; Segundo, Marcela A.
Abstract: The low bioavailability and nonspecific distribution of dapsone and clofazimine, commonly applied in combination for the treatment of leprosy, can produce toxic effects. Nanotechnological approaches enhance the delivery of these drugs. Therefore, a high‐performance liquid chromatography method was developed for the simultaneous determination of dapsone and clofazimine loaded in nanoformulations for quality control purposes. Chromatographic separation was achieved on a reversed‐phase Kinetex core‐shell C18 column, followed by spectrophotometric detection at 280 nm. Considering the different physicochemical properties of dapsone and clofazimine, elution was performed in gradient mode using an aqueous acetate buffer (50 mmol/L, pH 4.8) and an increasing acetonitrile content from 27 to 63% v/v at a flow rate of 1.0 mL/min with retention times of 6.2 and 14.0 min, respectively. The method was validated according to the European Medicines Agency guideline and it was found to be specific, accurate (99.6–114.0%), and precise for intra‐ (RSD ≤ 1.8%) and interday assays (RSD ≤ 12.5%). Both drugs showed stability after 24 h at room temperature and over three freeze–thaw cycles with recoveries ≥86.2%. Low temperature (4°C) in the autosampler caused the precipitation of clofazimine and must be avoided. The validated method was successfully applied in the quantification of both drugs in nanoformulations.